Revisiting Pathogen Exploitation of Clathrin-Independent Endocytosis: Mechanisms and Implications - Oliver Goldmann; Eva Medina (Cells)
Endocytosis is a specialized transport mechanism in which the cell membrane folds inward to enclose large molecules, fluids, or particles, forming vesicles that are transported within the cell. It plays a crucial role in nutrient uptake, immune responses, and cellular communication. However, many pathogens exploit the endocytic pathway to invade and survive within host cells, allowing them to evade the immune system and establish infection. Endocytosis can be classified as clathrin-mediated (CME) or clathrin-independent (CIE), based on the mechanism of vesicle formation. Unlike CME, which involves the formation of clathrin-coated vesicles that bud from the plasma membrane, CIE does not rely on clathrin-coated vesicles. Instead, other mechanisms facilitate membrane invagination and vesicle formation. CIE encompasses a variety of pathways, including caveolin-mediated, Arf6-dependent, and flotillin-dependent pathways. In this review, we discuss key features of CIE pathways, including cargo selection, vesicle formation, routes taken by internalized cargo, and the regulatory mechanisms governing CIE. Many viruses and bacteria hijack host cell CIE mechanisms to facilitate intracellular trafficking and persistence. We also revisit the exploitation of CIE by bacterial and viral pathogens, highlighting recent discoveries in entry mechanisms, intracellular fate, and host-pathogen interactions. Understanding how pathogens manipulate CIE in host cells can inform the development of novel antimicrobial and immunomodulatory interventions, offering new avenues for disease prevention and treatment.